1995
DOI: 10.1177/002199839502901101
|View full text |Cite
|
Sign up to set email alerts
|

Energy Release Rates for the ENF Specimen Using a Beam on an Elastic Foundation

Abstract: A new modified beam theory analysis is presented for the ENF specimen, which is used to evaluate the mode II delamination fracture toughness of fiber reinforced composite materials. The analysis combines the solution of a beam on a generalized elastic foundation to incorporate the effect of crack tip deformation, and a Timoshenko Beam Theory solution of the ENF to incorporate transverse shear on the predicted energy release rates. A distinctive feature of this approach is that crack tip deformation and shear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Corleto and Hogan [58] modelled the ENF test by considering the upper half laminate as a Timoshenko beam on a generalised elastic foundation consisting of extensional and rotational distributed springs. They found that the energy release rate is independent of the shear stiffness of the sublaminate, 5/6 GzxBh, but not of the shear modulus of the material, Gzx, which enters the expressions of the elastic constants of the foundation.…”
Section: Elastic-interface Modelsmentioning
confidence: 99%
“…Corleto and Hogan [58] modelled the ENF test by considering the upper half laminate as a Timoshenko beam on a generalised elastic foundation consisting of extensional and rotational distributed springs. They found that the energy release rate is independent of the shear stiffness of the sublaminate, 5/6 GzxBh, but not of the shear modulus of the material, Gzx, which enters the expressions of the elastic constants of the foundation.…”
Section: Elastic-interface Modelsmentioning
confidence: 99%
“…Wang and Williams [17] derived an additional length of V ℎ to the original crack length by introducing a correction factor V. Then the ERR was evaluated by the formulation of classical beam theory (CBT) using the adjusted crack length. Corleto and Hogan [5] employed two-parameter semi-infinite elastic foundation to the Timoshenko beam model to obtain the compliance and ERR of ENF specimens, in which the crack tip deformation was considered in their model. Ding and Kortschot [18] adapted a simplified analysis of a beam supported on a shear spring without accounting for the transverse shear deformation in order to find a simple and precise analytical solution.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…In the literature, there has been much study of fracture toughness [5][6][7][8][9][10][11][12][13]. However, it is the stable cracking problem that should be investigated in the interfacial debonding test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shu and Mai (1993) used both the "rigid" and "soft" joint models to evaluate the upper and lower bounds of buckling and vibration of bimaterial split beam. A better solution of compliance and ERR with consideration of local deformation at the crack tip (Williams, 1989;Wang and Williams, 1992;Corleto and Hogan, 1995;Ozil and Carlsson, 1999;Qiao et al, 2003a,b) was obtained by using a beam on elastic foundation model pioneered by Kanninen (1973Kanninen ( , 1974 and the local deformation was captured as the "elastic foundation effect" with two foundation stiffness coefficients. However, the beam on elastic foundation model could only be employed to model one sub-beam.…”
Section: Introductionmentioning
confidence: 99%